RESIDU PUPUK NITROGEN DI LINGKUNGAN PERAIRAN HULU DAERAH ALIRAN SUNGAI TONDANO PROVINSI SULAWESI UTARA - Wantasen, Sofia (Bumi Lestari, 2016)
The Nitrogen fertilizer which is not absorbed by plant will be impact to residue in  the environment.  The aim of this study was to assess the residues of nitrogen in the aquatic environment up stream of the Tondano Watershed during 2013-2015 (three years).  Data collected by observation of agriculture activity and determination of sampling by using composite sampling method in River Panasen which is paddy irrigation outlet canal up stream of the Tondano Watershed during 2013-2015 (three years), was measurement each three month and analysis nitrate, nitrite, ammonia in the Laboratory.   Method data analysis are Graphic Method and to compare with standart Goverment PP. No. 82/2001 Class II. Results showed that the nitrogen residue concentration (nitrate, nitrite, ammonia) at aquatic environment in the up stream of Tondano Watershed on the growing season in 2013 nitrate concentration: 0,293-0,408 mg/l; nitrite 0,001-0,041 mg/l; ammonia 0,04-0,28 mg/ l. in the growing season in 2014  concentration nitrate: 0,184-0,628 mg/l; nitrite 0,020,077 mg/l; ammonia 0,002-0,13 mg/l. in the growing season in 2015 concentration nitrate: 0,173-0,585 mg/l; nitrite 0,001-0,029 mg/l; ammonia 0,05-0,10 mg/l.
Keywords: residue, nitrogen fertilizer, outlet irrigation, Tondano Watershed